Tumor microenvironmental cytokines bound to cancer exosomes determine uptake by cytokine receptor-expressing cells and biodistribution - Luize G. Lima (Nature Portfolio, 2021)
Cancer derived exosomes are reported to promote metastatic dissemination. Here the authors show that cytokines in the tumor microenvironment bind to exosomes via glycosaminoglycan side chains of proteoglycans, and these exosomes are preferentially taken up by specific cell lineages and organs to promote metastasis.